Knowledge, Attitudes, Ownership, and Utilization of Mosquito Nets among Mothers/Caregivers of under Five Children in South Sudan - Jacob, Amanya; Dau, Atemthi D.; Apary, Ezbon W.; Nshakira, Nathan (International Journal of Child Health and Nutrition, 2026)
Background: Malaria is a leading cause of illness and death in under five and pregnant women. Despite insecticide-treated nets’ mass distribution, their utilization is low. ITNs persisted in a preventive intervention and a physical barrier to mosquitoes. We explore fever prevalence, health-seeking, knowledge, attitudes, practices, and ITN ownership and utilization among mothers/caregivers of U-5 children in South Sudan. Methods: A community-based descriptive cross-sectional survey was implemented in 23 counties with high malaria incidences. Mothers/caregivers of U-5 were recruited. A multi-stage cluster random sampling technique was used. Trained enumerators were employed to administer a questionnaire adopted from the malaria indicator survey. Kobo collects v.2022.2 was used, and SPSSTM 27 was used for analysis. Results: A total of 466 interviews were completed, bypassing 460 sample size estimates. Of 466, 89.3% (n=416) were mothers/caregivers of U-5. 73% were females. The majority is 25-34 years old, with 34.3% (95% CI 30 - 39). 60.1% had no formal education, 91.8% (89.5 - 94.2) were employed in the private sector, and Fever prevalence in U-5 was 56.1%. Treatment was sought for 59.2% of U-5 with fever, and 25.1% received timely care. 46% received treatment from a government hospital, 9% from private, and 44.9% received ACT. Utilization of any nets and ITNs was 72% and 69.4%. Overall ownership and usage were 72.3% and 71.9%; 73.1% of females used ITNs, and 72.2% were religious believers. 94% U-5 with at least one ITN slept under an ITN last night. Conclusion: The majority of respondents had a better understanding of malaria prevention but poor seeking behavior. Low ownership and utilization of ITNs were revealed. Thus, improvement in community education towards early treatment-seeking and ITN usage is required. Our findings would be useful for effective treatment, response to control, and prevention in highly endemic zones of South Sudan.